2018
DOI: 10.1021/acs.iecr.8b03776
|View full text |Cite
|
Sign up to set email alerts
|

AIE-Active Fluorescent Nonconjugated Polymer Dots for Dual-Alternating-Color Live Cell Imaging

Abstract: Fine-tuning emission fluorescent bioprobes are highly desirable but still scarce for dual-alternating-color live cell imaging. Herein, a facile strategy has been reported to develop a dual-color nanoprobe for targeted cancer cell imaging. A new kind of nonconjugated polymer dots (Pdots) is prepared by the solution self-assembly of an amphiphilic 4-arm star polymer TPE-tetraPNIPAM-Eu(III) in aqueous media. The asprepared Pdots show two well-separated emission peaks with a wavelength difference of 195 nm and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…8 Fluorescent imaging reagents which give cellular images with two different colours, can distinguish sites of interest from false positive signals generated by adventitious fluorescent biomolecules in the monitoring processes. 9 They can also allow for in situ fluorescence based ratiometric reporting of cell conditions such as pH, temperature, hydrophilicity/phobicity, or oxygen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…8 Fluorescent imaging reagents which give cellular images with two different colours, can distinguish sites of interest from false positive signals generated by adventitious fluorescent biomolecules in the monitoring processes. 9 They can also allow for in situ fluorescence based ratiometric reporting of cell conditions such as pH, temperature, hydrophilicity/phobicity, or oxygen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, 50% or more semiconducting polymer (by volume or weight) is important because it distinguishes Pdots as NPs derived from a photoluminescent material rather than a doped host polymer. That said, there are also examples where “Pdot” refers to luminescent NPs composed of non-semiconducting polymer materials where PL arises from cross-link-enhanced emission, aggregation-induced emission (AIE) Pdots (or AIE dots), , or pendent fluorophores …”
Section: Catalog Of Materialsmentioning
confidence: 99%
“…Due to its dual emission property, blue light at 630 nm and red light at 395nm make it a promising candidate for cell imaging of HeLa cells, A549, and HepG2 cells upon incubation with AIE Pdots. The cytotoxicity studies revealed 90% cell viability Figure 15 [ 91 ].…”
Section: Aie Active Molecules For Biological Cell Imagingmentioning
confidence: 99%